2013
DOI: 10.3899/jrheum.120814
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G 3′ Untranslated Region Polymorphisms Are Associated with Systemic Lupus Erythematosus in 2 Brazilian Populations

Abstract: These results indicate that HLA-G 3'UTR polymorphic sites, particularly +3142G and +3010C alleles, were associated with SLE susceptibility, whereas UTR-1 was associated with protection against development of SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 42 publications
7
31
1
1
Order By: Relevance
“…For instance, according to our results, UTR-5 and UTR-7 frequencies are higher in recurrent pregnancy loss [50], whereas UTR-1 has been associated with reduced risk of recurrent pregnancy loss [51]. Besides, 3’UTR variants have been identified as potential prognostic biomarkers to determine susceptibility to infections [52, 53],the success of transplantation [54], and the outcome of cancer [55] and autoimmune diseases [56]. Even if we cannot neglect the influence of the HLA-G 5’URR haplotypes that are in linkage disequilibrium with 3’UTR [18], here we demonstrated that 3’UTR variants are directly involved in the differential response to cellular endogenous factors and are therefore potential target sites to consider for the design of novel therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, according to our results, UTR-5 and UTR-7 frequencies are higher in recurrent pregnancy loss [50], whereas UTR-1 has been associated with reduced risk of recurrent pregnancy loss [51]. Besides, 3’UTR variants have been identified as potential prognostic biomarkers to determine susceptibility to infections [52, 53],the success of transplantation [54], and the outcome of cancer [55] and autoimmune diseases [56]. Even if we cannot neglect the influence of the HLA-G 5’URR haplotypes that are in linkage disequilibrium with 3’UTR [18], here we demonstrated that 3’UTR variants are directly involved in the differential response to cellular endogenous factors and are therefore potential target sites to consider for the design of novel therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between HLA-G 3′UTR polymorphisms (especially for the 14 bp polymorphism) and other variable sites in the HLA-G coding and promoter region was also previously explored [77, 78, 105, 112, 113]. Furthermore, several populations were evaluated regarding these polymorphic sites, including additional samples from other Brazilian regions and other worldwide populations, and the same pattern of 3′UTR variability has been observed [6, 27, 28, 85, 102, 114121]. Recently, the variability at the HLA-G locus was explored by using the 1000 Genomes data [28, 102] and, taking together all of these studies in the last decade, it became clear that the same 3′UTR pattern observed in Brazilians [27] is found worldwide, with just some new low frequency haplotypes.…”
Section: Posttranscriptional Regulation Of Hla-gmentioning
confidence: 98%
“…The +3187 A/G polymorphism is close to (4-bp upstream) an AU-rich motif and has been associated with decreased in vitro mRNA stability, so that the presence of the +3187A allele may lead to decreased HLA-G expression [15]. Recent studies have reported that the presence of the +3187 A allele is associated with preeclampsia in a Canadian population [15] and with systemic lupus erythematosus in Northeastern Brazilian patients [30]. …”
Section: Introductionmentioning
confidence: 99%